Net Effect of Young Adult Dual Combusted Cigarette and E-Cigarette Users’ Anticipated Responses to Hypothetical E-Cigarette Marketing Restrictions - Glantz, Stanton A. (Subst Use Misuse, 2020)
BACKGROUND: Dual use of e-cigarettes and cigarettes is common among young adults. Earlier research has used an internet panel to assess anticipated effects of eliminating nicotine, flavors (except menthol), and customizable e-cigarettes on predicted changes in e-cigarette and cigarette consumption. This earlier analysis showed that all these policies were predicted to lower e-cigarette consumption and increase cigarette consumption among these dual users. The earlier analysis, did not, however, estimate the net effect of these policies considering both lowered and increased consumption. METHODS: We computed the net effects of these policies as the difference between people predicting quitting or using cigarettes less and those predicting that they would use them more. The same calculations were done for e-cigarettes. Significance testing was done with z-tests. RESULTS: As expected, the net effect of all three policies was to significantly lower e-cigarette consumption. The net effect was to also lower cigarette consumption for eliminating nicotine and flavors in e-cigarettes, with no significant net effect of eliminating modifiable e-cigarettes. CONCLUSION: Eliminating nicotine and flavors from e-cigarettes is predicted to lower cigarette as well as e-cigarette consumption.